Utveckling av en skalbar webbapplikation i JavaScript och ReactJs - EDENHOLM, JOHANNES (My University, 2018)
IGDB is a company intending to collect all essential data about games in the same place. The codebase for the current website is messy, old and restrictive. Developers have difficulty creating new functionality and managing the old. This report describes a work with the purpose of creating a new code base in JavaScript using the library, ReactJs. The work is limited to front-end development as everything else is dealt with using IGDB's own API. This project covers the implementation of components with the help of React as library and material-UI as basis for the user interface. The work also covers the method and implementation describing how the work has been carried, what has been used and how it has been used. The report also covers an evaluation of the final product and a discussion of whether other options may have been possible to achieve the same result.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science